Securing utility computing using enhanced elliptic curve cryptography and attribute-based access control policy. (20th August 2022) - Varghese, Saira; Vigila, S. Maria Celestin
This paper proposes a data security model for utility computing that integrates securely mapped plain text using Elliptic Curve Cryptography (ECC) without certified keys, attribute-based access control using Reduced Ordered Binary Decision Diagram (ROBDD), cryptographically secure 256 bit pseudorandom numbers and fingerprint security. ECC uses standard elliptic curves of large prime and ROBDD is built with positive and negative attributes of data users and 256 bit pseudorandom secrets along its path. Secret key that is generated based on the attributes along the valid path of the policy enhances the security. The proposed model allows secure key exchange by making use of the property of elliptic curve to convert numbers to points and secure data storage by associating authenticated secrets of end users with the original secret key is beneficial in decentralised architecture. The result reveals that proposed model achieved high security and less space and time complexity for securing cloud data.